2016
DOI: 10.1016/j.jamcollsurg.2015.12.013
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of Adjuvant Mitotane after Resection of Adrenocortical Carcinoma: A 13-Institution Study by the US Adrenocortical Carcinoma Group

Abstract: BACKGROUND Current treatment guidelines recommend adjuvant mitotane after resection of adrenocortical carcinoma with high-risk features (eg, tumor rupture, positive margins, positive lymph nodes, high grade, elevated mitotic index, and advanced stage). Limited data exist on the outcomes associated with these practice guidelines. STUDY DESIGN Patients who underwent resection of adrenocortical carcinoma from 1993 to 2014 at the 13 academic institutions of the US Adrenocortical Carcinoma Group were included. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 42 publications
2
61
1
1
Order By: Relevance
“…Promising results with mitotane treatment were initially received with enthusiasm, 3 however, additional studies have failed to replicate these findings consistently. 4,5 Therefore, surgery remains the mainstay of treatment in patients with resectable primary ACC, with 5-year survival rates reaching 65% after margin-negative resection. 6 However, even after curative resection of ACC, recurrence of disease is relatively common and can be detected in approximately two-thirds of patients after a median time to recurrence of 19 months.…”
mentioning
confidence: 99%
“…Promising results with mitotane treatment were initially received with enthusiasm, 3 however, additional studies have failed to replicate these findings consistently. 4,5 Therefore, surgery remains the mainstay of treatment in patients with resectable primary ACC, with 5-year survival rates reaching 65% after margin-negative resection. 6 However, even after curative resection of ACC, recurrence of disease is relatively common and can be detected in approximately two-thirds of patients after a median time to recurrence of 19 months.…”
mentioning
confidence: 99%
“…Of note however, only 32/88 (36%) patients who received mitotane in this study had serum mitotane levels available, of which only 15 patients had levels between 14–20 mg/L. Thus, no definitive conclusions can be drawn from this study (19). With similar controversial results noted in small prospective studies (20, 21), there is an urgent need for large randomized prospective trials evaluating the efficacy of mitotane in the adjuvant setting.…”
Section: Current Therapies For Accmentioning
confidence: 83%
“…Therefore, adjuvant mitotane therapy and local radiotherapy were initiated. Whereas, the 13 institutions study concluded that there's no association between adjuvant mitotane after resection and improvement of recurrence-free survival or overall survival (20).…”
Section: Discussionmentioning
confidence: 99%